2015
DOI: 10.1093/mnras/stv1981
|View full text |Cite
|
Sign up to set email alerts
|

A self-consistent, absolute isochronal age scale for young moving groups in the solar neighbourhood

Abstract: We present a self-consistent, absolute isochronal age scale for young ( 200 Myr), nearby ( 100 pc) moving groups in the solar neighbourhood based on homogeneous fitting of semi-empirical pre-main-sequence model isochrones using the τ 2 maximumlikelihood fitting statistic of Naylor & Jeffries in the M V , V − J colour-magnitude diagram. The final adopted ages for the groups are: 149 +51 −19 Myr for the AB Dor moving group, 24 ± 3 Myr for the β Pic moving group (BPMG), 45 +11 −7 Myr for the Carina association, 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
561
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 522 publications
(632 citation statements)
references
References 142 publications
70
561
1
Order By: Relevance
“…15 Myr for the system, consistent with the age of the βPictoris moving group (24±3 Myr; Bell et al 2015a). They, however, obtain a dynamical mass for GJ3305B that is discrepant with that of evolutionary models, which they suggest could be explained by the presence of an unresolved companion.…”
Section: Likely Linear Trends In Rv Curvessupporting
confidence: 57%
See 1 more Smart Citation
“…15 Myr for the system, consistent with the age of the βPictoris moving group (24±3 Myr; Bell et al 2015a). They, however, obtain a dynamical mass for GJ3305B that is discrepant with that of evolutionary models, which they suggest could be explained by the presence of an unresolved companion.…”
Section: Likely Linear Trends In Rv Curvessupporting
confidence: 57%
“…The young sample was constructed by selecting K-to mid-M-type young stars in the solar neighborhood, mainly from known members of young moving groups, such as βPictoris (24±3 Myr; Zuckerman et al 2001;Bell et al 2015a), ABDoradus ( -+ 149 19 51 Myr; Zuckerman et al 2004;Bell et al 2015a), and the Octans-Near association (≈30-100 Myr; Zuckerman et al 2013), with Two Micron All Sky Survey (2MASS) K S -band magnitudes brighter than 7.1 (the brightest target, εEridani, has K S =1.8) so that an S/N of ∼80 could be achieved within approximately an hour. The young age of all stars in this sample is strongly constrained by kinematic membership in these young associations, typically in addition to lithium abundance measurements or comparison to isochrones (e.g., Torres et al 2008), except for the starεEridani, which is not a member of any known young moving group.…”
Section: The Young Samplementioning
confidence: 99%
“…While studies of younger (10-15 Myr) clusters show significant amounts of disc emission around many M dwarfs (e.g. Currie et al 2008), Simon et al (2012) found no disc excesses in the M dwarf population of Tucana Horologium (45 ± 4 Myr, Bell, Mamajek & Naylor 2015) and AB Dor (149 +51 −19 Bell et al 2015). Hence, the lack of disc excess indicates that 2MASS J0213+3648 AB is older than around 20 Myr.…”
Section: The Age Of 2mass J0213+3648 Abmentioning
confidence: 87%
“…The availability of Gaia DR1 data sets (Gaia Collaboration et al 2016a) as well as the recent revision of the ages of several young moving groups used as reference (Bell et al 2015) calls for a reassessment of the stellar properties. We also exploit photometric time series to refine the Article number, page 4 of 15 Allard et al (2012) and assuming an age of 35 Myrs.…”
Section: Stellar Propertiesmentioning
confidence: 99%